PENGARUH KARAKTER EKSEKUTIF TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE) (Studi Empiris pada Perusahaan Manufaktur yang listing di Bursa Efek Indonesia Tahun 2010-2012 - Irin Dwi Mmaryani, 10.05.52.0086; Badjuri, Achmad (Students Journal of Accounting and Banking, 2014)
This study aims to analyze the influence of the executive character of the Tax Avoidance in companies listed on the Indonesia Stock Exchange (IDX).In this study population are used throughout the manufacturing companies listed on the Indonesia Stock Exchange (IDX) of the years 2010 to 2012. The sampling technique using purposive sampling. Mechanical testing data is to use a multiple linear regression analysis.The analysis showed that the variables Size, Leverage and NOL (Net Operating Loss) as independent variables have a significant influence on Tax Avoidance. While variable and Sales Growth Risk Taker has no significant effect on Tax Avoidance.Keywords: Risk Taker, Size, Leverage, Sales Growth, NOL (Net Loss Opetaing) and Tax Avoidance